Environmental inspection agro tech – guarantee sustainable development agricultural systems - Makarenko, Natalia; Bondor, Valeria; Makarenko, Volodymur (Acta Agraria Debreceniensis, 2012)
Shown the expediency of the environmental expertise technologies of growing crops in terms of impact on soil fertility, crop phytosanitary status, quality, chemicals migration, biological soil activity, crop productivity, which ensure avoidance of adverse impact on the environment and human health.